The Concept of “Halalan Thayyiban” Food in the Qur’an and Its Relevance to Physical Health - anjany, Selvia (Maliki Interdisciplinary Journal, 2026)
The concept of consumption in Islam does not merely rely on fulfilling biological needs but represents a holistic integration involving spiritual dimensions, legal formality, and material health. This study aims to analyze in depth the semantic review of the three pillars of words: kulu (consumption), halal (legality of ingredients), and thayyib (quality of goodness) based on Surah Al-Baqarah verse 168, to identify the substantive requirements of good food, and to formulate its empirical relevance to physical and spiritual vitality. The method used in this article is a literature review (library research) with a content and semantic analysis approach toward holy texts and nutritional health literature. The results show that Surah Al-Baqarah: 168 establishes dual standards in consumption: formal-legal standards (halal) and health-quality standards (thayyib). Semantically, halal refers to anything released from the bonds of Sharia prohibition (al-ibahah), while thayyib encompasses aspects of purity, optimal nutritional value, process hygiene, and freedom from doubtful elements (shubhat). Neglecting the thayyib aspect has tangible implications for the decline of modern generational health, including metabolic dysfunction and early-onset degenerative diseases. Conversely, fulfilling the halalan thayyiban criteria directly contributes to preventing diseases from pathogenic bacteria, optimizing brain function (neuroplasticity), hormonal balance, and emotional-spiritual stability. This study concludes that halalan thayyiban is a preventive-holistic approach that sustainably unifies human physical and mental health.